2001
DOI: 10.1016/s1010-7940(01)00610-8
|View full text |Cite
|
Sign up to set email alerts
|

Sternal wound complications after primary isolated myocardial revascularization: the importance of the post-operative variables

Abstract: Reoperation, nephrological and pulmonary problems are strong predictors, obesity and age independent preoperative risk factors for sternal wound complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 11 publications
1
11
2
Order By: Relevance
“…Reston et al [32] in a meta-analysis of 53 studies involving a total of 46 621 patients, found a lower incidence of wound complications, including superficial and deep infection in patients undergoing off-pump compared with on-pump CABG. The cardiopulmonary bypass time is a variable related to the duration of surgical procedure, and it was demonstrated as a possible risk predictor in some studies [33]. Although recognized in the literature as a possible risk factor, we observed no significant association between a prolonged cardiopulmonary bypass time and higher incidence of mediastinitis.…”
Section: Discussioncontrasting
confidence: 74%
“…Reston et al [32] in a meta-analysis of 53 studies involving a total of 46 621 patients, found a lower incidence of wound complications, including superficial and deep infection in patients undergoing off-pump compared with on-pump CABG. The cardiopulmonary bypass time is a variable related to the duration of surgical procedure, and it was demonstrated as a possible risk predictor in some studies [33]. Although recognized in the literature as a possible risk factor, we observed no significant association between a prolonged cardiopulmonary bypass time and higher incidence of mediastinitis.…”
Section: Discussioncontrasting
confidence: 74%
“…A previous study done by our group found that obesity is an independent preoperative risk factor for sternal wound complications after CABG [23]. This is in association with Lu et al and Schwann et al [24,15].…”
Section: Morbiditysupporting
confidence: 78%
“…A practical point in the discussion about sternal wound problems is the use of different sternal closing techniques. In this series, however, all patients' sternal closure was performed using twisted stainless steel wires and in our previous study we could not find a relation between techniques of sternal closure and sternal wound problems [23]. Another point is the influence of off-pump surgery (group A 2/30 (6.6%) versus 15/176 (8.5), group B 4/131 (3.0%) versus 37/793 (4.9%)).…”
Section: Morbiditymentioning
confidence: 54%
See 1 more Smart Citation
“…The cardiopulmonary bypass time is a variable related to the duration of surgical procedure, and it was demonstrated as a possible risk predictor in some of the studies [14]. However, the present study, in fact, does not establish such an observation as being the truth, once there were no control group CPB analyses (nonmediastinitis group) to compare with.…”
Section: Discussioncontrasting
confidence: 60%